The Attitude of Low-Proficiency Learners Towards Translanguaging Practices in The EFL Classroom - Fitri Dwi Prastiwi; Izzati Gemi Seinsiani (PROJECT (Professional Journal of English Education), 2026)
This study examines the attitudes of low-proficiency learners towards translanguaging practices in an EFL classroom in Indonesia, where exposure to English is mostly limited to formal instruction. A qualitative descriptive design was employed, with data collected through semi-structured interviews involving one teacher and ten low-proficiency learners. The findings indicate that learners generally hold positive attitudes towards translanguaging, as it facilitates understanding of instructional content, reduces anxiety, and creates a more supportive learning environment. The use of both Indonesian and English in an English class has been shown to facilitate comprehension of explanations, support the acquisition of new vocabulary, and enhance learners' confidence in participating in classroom activities. However, enhanced comprehension does not necessarily translate into active participation, as restricted vocabulary and diminished confidence remain significant impediments. Learners' attitudes are predominantly shaped by their linguistic challenges and the pedagogical approaches instructors employ in implementing translanguaging. Translanguaging can be regarded as an inclusive pedagogical approach that fosters both comprehension and emotional engagement, particularly among learners with limited proficiency. It is recommended that further research be conducted in order to explore the role of shadow teachers in supporting translanguaging practices, providing individualized scaffolding, and enhancing learners' participation and confidence in using English more actively.